Factores de riesgo y su relación con infecciones respiratorias bajas en niños ingresados en el área de pediatría Hospital General Guasmo Sur, Guayaquil. Diciembre 2022 - mayo 2023 - Alcívar Lima, Victoria Isabel (2023)
Lower respiratory tract infection is the leading cause of hospitalization and mortality among children under 5 years of age in developing societies. The incidence of lower respiratory tract infection is also high in the developed world, but the most severe forms of illness and mortality are disproportionately high among developing countries; despite this, there are no current studies on risk factors and their relationship with lower respiratory infections in children admitted to the pediatric area of the General Hospital Guasmo Sur in the city of Guayaquil in the period from December 2022 to May 2023. Aim: To identify the risk factors and their relationship with lower respiratory infections in children admitted to the pediatric area at the Guasmo Sur General Hospital in the city of Guayaquil during the period from December 2022 to May 2023. Methodology: The research will be based on a mixed quantitative-qualitative methodological approach and will be an applied, field, exploratory-descriptive and cross-sectional research. Conclusion: The risk factors associated with lower respiratory infections in the admissions found at the Guasmo Sur hospital were: child malnutrition (45%), vitamin A deficiency (24%), lack of breastfeeding (20%), low birth weight (8%), and passive smoking (3%).